2020
DOI: 10.1136/bmjgast-2020-000532
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of glucocorticoid-induced hyperglycaemia in inflammatory bowel disease: metabolic and clinical predictors identified by machine learning

Abstract: BackgroundGlucocorticosteroids (GC) are long-established, widely used agents for induction of remission in inflammatory bowel disease (IBD). Hyperglycaemia is a known complication of GC treatment with implications for morbidity and mortality. Published data on prevalence and risk factors for GC-induced hyperglycaemia in the IBD population are limited. We prospectively characterise this complication in our cohort, employing machine-learning methods to identify key predictors of risk.MethodsWe conducted a prospe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
4
0
2
Order By: Relevance
“…Moreover, it was demonstrated that machine learning methods may be applied to identify risk of therapy complications in IBD. For instance, McDonell et al demonstrated that random forest (RF) regression models identified higher levels of CRP and longer duration of disease as predictors for hyperglycemia in IBD patients treated with intravenous glucocorticosteroids [ 16 ]. In turn, Choi et al developed a machine learning model to predict the five-year risk of starting biologic therapy in IBD patients [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was demonstrated that machine learning methods may be applied to identify risk of therapy complications in IBD. For instance, McDonell et al demonstrated that random forest (RF) regression models identified higher levels of CRP and longer duration of disease as predictors for hyperglycemia in IBD patients treated with intravenous glucocorticosteroids [ 16 ]. In turn, Choi et al developed a machine learning model to predict the five-year risk of starting biologic therapy in IBD patients [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the severity of inflammation, colorectal surgeons were asked to review the patient to consider colectomy, as supportive care with systemic steroids and exclusive enteral nutrition did not lead to an improvement in the patient’s condition after 3 days. Intravenous steroids were stopped due to lack of efficacy, hyperglycaemia9 and concerns of increasing perioperative complications in case of colectomy. This was an IBD multidisciplinary team (MDT) decision in this individual case and it should be noted that systemic steroids are an important therapy in severe ulcerative colitis management 10.…”
Section: Case Presentationmentioning
confidence: 99%
“…Кроме того, у некоторых пациентов на протяжении всего заболевания наблюдаются множественные сопутствующие заболевания, связанные в том числе с длительным приемом кортикостероидов (сахарный диабет, остеопороз, надпочечниковая недостаточность и др. ), которые часто применяют у больных с субоптимальным клиническим ответом [5].…”
Section: сокращенияunclassified
“…Эффективность и безопасность двой ной терапии -биологической и малыми молекулами у пациентов с язвенным колитом (стр. [5][6][7][8][9][10][11][12] To article Effi cacy and safety of dual therapy -biological and small molecules in patients with ulcerative colitis (p. 5-12)…”
unclassified